2013
DOI: 10.1111/imj.12063
|View full text |Cite
|
Sign up to set email alerts
|

B‐type natriuretic peptide levels are decreased by reducing dietary salt intake in patients with compensated heart failure with preserved ejection fraction

Abstract: Changes in BNP levels were associated with changes in the estimated daily salt excretion in outpatients with compensated heart failure. Salt restriction may be beneficial for the management of patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recently it has been reported that higher NT-proBNP is independently associated with the presence of OSA, 18 which is one of the causes of nocturia. 19 Excess sodium intake may also be involved in this association, because restriction of sodium intake has been reported to reduce BNP, 20 nocturnal urine volume, 21 and nocturia. 22 In addition, abnormal circadian BP patterns may at least partially be involved in the mechanism of the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been reported that higher NT-proBNP is independently associated with the presence of OSA, 18 which is one of the causes of nocturia. 19 Excess sodium intake may also be involved in this association, because restriction of sodium intake has been reported to reduce BNP, 20 nocturnal urine volume, 21 and nocturia. 22 In addition, abnormal circadian BP patterns may at least partially be involved in the mechanism of the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Our data analysis showed that only 5 % HF patients fully adhered to the sodium restriction guideline (≤1500 mg per day). BNP and sodium intake are highly correlated [ 32 ]. Without fully complying with the sodium restriction guideline, it would be highly unlikely to observe significant changes in clinical biomarkers (BNP or urine sodium/ creatinine ratio).…”
Section: Discussionmentioning
confidence: 99%
“…The significant decrease in NT‐proBNP in Group B does not appear to be related to changes in cardiac morphology because Diet Group B did not have significant reductions in left ventricular hypertrophy. The change in NT‐proBNP in Group B also might be related to variability in NT‐proBNP measurements, which has been shown in dogs, or to changes in dietary sodium intake . Dietary sodium (on a mg/100 kcal basis) decreased significantly for all 29 cats as a group, and individually for Diet Groups A and B.…”
Section: Discussionmentioning
confidence: 82%
“…The change in NT-proBNP in Group B also might be related to variability in NT-proBNP measurements, which has been shown in dogs, 14 or to changes in dietary sodium intake. 15 Dietary sodium (on a mg/100 kcal basis) decreased significantly for all 29 cats as a group, and individually for Diet Groups A and B. The current study did not measure absolute food intake, which would have allowed for calculation of sodium intake on a mg/day basis and is a limitation, but the fact that the median sodium content of the diet decreased significantly suggests that cats were likely to also have a decrease in their total daily sodium intake.…”
Section: Discussionmentioning
confidence: 99%